2019
DOI: 10.1088/2515-7620/ab4a85
|View full text |Cite
|
Sign up to set email alerts
|

20 cm resolution mapping of tundra vegetation communities provides an ecological baseline for important research areas in a changing Arctic environment

Abstract: Arctic tundra vegetation communities are spatially heterogeneous and may vary dramatically from one meter to the next. Consequently, representing Arctic tundra vegetation communities accurately requires very high resolution raster maps (<5 m grid cell size). However, using remotely sensed data to produce maps with sufficient spatial detail at an extent appropriate for understanding landscape-scale ecological patterns is challenging. In this study, we used predictor layers derived from airborne lidar and high-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In this exploratory study, we primarily investigated the interoperability of deep learning model predictions across heterogeneous tundra landscapes. Arctic tundra vegetation exhibits a significantly higher degree of heterogeneity over small spatial scales [ 52 ]. Further research is needed to better understand how trained models behave across other tundra vegetation types and regions.…”
Section: Model Evaluation Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this exploratory study, we primarily investigated the interoperability of deep learning model predictions across heterogeneous tundra landscapes. Arctic tundra vegetation exhibits a significantly higher degree of heterogeneity over small spatial scales [ 52 ]. Further research is needed to better understand how trained models behave across other tundra vegetation types and regions.…”
Section: Model Evaluation Results and Discussionmentioning
confidence: 99%
“…In future research, we aim to systematically probe further into model interoperability considering multi-faceted factors. Moreover, Arctic tundra landscapes cover spatially isolated ponds, lakes, marshes, river, and stream corridor wetlands, which representing highly heterogeneous features, varying in soil moisture, vegetation composition, elevation, surficial geology, ground ice content, soil thermal regimes and surface hydrology [ 51 , 52 ]. Fine-scale differences in microtopography, limit the ability to comprehend local scale controls on regional to global scale patterns which, is an important factor in characterizing IWPs in Arctic varying tundra areas [ 62 ].…”
Section: Model Evaluation Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Land cover maps with classifications designed for Arctic vegetation types are typically limited in spatial or temporal range (Chasmer et al, 2014;Greaves et al, 2019), precluding comprehensive study of Arctic vegetation dynamics, or are coarse in spatial or temporal resolution (e.g., gridded 1 km CAVM) (Raynolds et al, 2019), precluding accurate characterization of the high level of spatial heterogeneity and temporal variability in Arctic vegetation. Bartsch et al (2016) suggested that a 30 m spatial grain, which is the proposed spatial resolution for SBG, is sufficient for capturing many of the dynamics of Arctic land cover.…”
Section: Land Cover and Vegetation Classificationmentioning
confidence: 99%
“…poor data coverage outside of North America (Neigh et al, 2013;Nelson et al, 2009); (2) inconsistent coverage by key global imaging systems, including imaging spectroscopy (IS), thermal infrared (TIR), Lidar, and synthetic aperture radar (SAR)-as they are not available, have poor spatial coverage, coarse resolution, or have not regularly covered northern high latitudes; and (3) the fact that the low species diversity in the ABR is offset by high sub-pixel heterogeneity (Greaves et al, 2019;Riihimäki et al, 2019;Yang, Meng, et al, 2020).…”
Section: Veg E Tati On Comp Os Iti On and Dis Tributionmentioning
confidence: 99%